Evaluasi kondisi struktur beton bertulang dengan menggunakan half cell potential test pada bangunan kantor di pinggir Pantai Ancol - Zel Citra; Yosie Malinda; Paksi Dwiyanto Wibowo; Suci Putri Elza; Risma Apdeni (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
Measurement of half cell potential is commonly used for the assessment of the resistance of reinforced concrete where corrosion of the reinforcement is predicted. The standards used in the test are ASTM C876-91: Standard Test method for half-Cell Potential of Uncoated Reinforcing Steel in Concrete and ACI 222R-01: Protection of Metal in Concrete Against Corrosion. Furthermore, the carbonation of the reinforcement in the concrete which is caused by a chemical reaction between calcium in the concrete and sulfate salts from the outside make the concrete mass is pushed and broken. The results of testing the reinforced concrete structures of office buildings on the Ancol waterfront, some of the carbonation that occurs has exceeded the concrete cover. The results of the Half Cell Potential test 1, 2, 6, 8, 9, and 10 show that the corrosion rate of the reinforcement in the concrete is <10% with type 3, namely "humid, chloride free concrete", where the concrete is moist and not contaminated chloride, which means that the corrosion rate of steel reinforcement in concrete is quite low. The results of the Half Cell Potential 3, 4, 5, and 7 tests show that the corrosion rate of the reinforcement is between 10% - 90% with type 4, namely "humid, carbonated concrete", where the concrete is moist and carbonated but the corrosion rate is not too high.